UPAYA PEMANFAATAN TEKNOLOGI: APLIKASI RPP DIGITAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) (STUDI KASUS SEKOLAH INDONESIA KUALA LUMPUR (SIKL)) - Nurul Hikmah Luthfiyana; Yuliana - -; Eva Syafa'atul Husna; Nailul - Hidayah; Shela Khofiyan Nida; Rakanita Dyah Ayu Kinesti (JKPD (Jurnal Kajian Pendidikan Dasar), 2022)
The development of Science and Technology increasingly encourages renewal efforts in the use of technology results in the teaching and learning process.  In implementing good learning, we must maximize all learning media in order to achieve learning outcomes.  Thus this learning media can be used as a support and coupling for teaching materials in improving the quality of education.  The Digital RPP application is a technology use to maximize the increase in learning at the Kuala Lumpur Indonesian School (SIKL).  The Digital RPP application aims to facilitate teachers in the teaching and learning process in the current pandemic era.  This study uses a descriptive analytical research method, the research approach uses qualitative studies, with an overview that can find out the efforts to use the Digital RPP Application.  The results showed that the Digital RPP application is useful for teachers so that it has easy access to interactive and fun learning resources.  Thus the Digital RPP application is the main solution for teachers in making lesson plans for that to use technology is highly recommended to improve the quality of education at the Kuala Lumpur Indonesian School (SIKL).